Materials and technology a systematic encyclopedia of the technology of materials used in industry and comerce, including foodstuffs and fuels based upon a work originally devised by the late Dr. J.F. van Oss : air, water, inorganic chemicals and nucleonics. (Longmans J.H. Debussy, 1968)
Volume I